An integrated approach to determining the risk of developing preeclampsia in pregnant women with hypertensive conditions (CARDIOLOGY OF UZBEKISTAN, 2025)
Aim. Hypertensive disorders complicate one in ten pregnancies, which necessitates the development of new standards for determining the risk of preeclampsia and heart failure in pregnant women. To determine early clinical markers in pregnant women with gestational arterial hypertension (GAH) as sensitive diagnostic criteria for the development of hypertensive complications. Materials and methods. The study included 91 pregnant women of the 2nd-3rd trimesters, divided into groups: healthy pregnant women (n=44) and with GAH (n=47) according to the ESC Guidelines 2018. Physical examination, blood pressure measurement, BMI calculation, detailed blood tests including lipidogram, coagulogram, determination of prolactin and NT-proBNP, echocardiography, vascular stress test to assess endothelial function were performed. Results. Pregnant women with GAH were found to have morphofunctional changes in the heart, early signs of endothelial dysfunction, lipid and carbohydrate metabolism disorders. Microalbuminuria demonstrated high diagnostic value for detecting early renal dysfunction. The prognostic significance of prolactin and NT-proBNP levels was established. Conclusion. Comprehensive early monitoring of clinical and biochemical parameters of pregnant women with GAG is necessary for timely detection of preeclampsia predictors. The results contribute to the improvement of diagnostic and preventive standards for the management of this cohort of patients.